POSITIVISME SEBAGAI ERA BARU FILSAFAT DAN PENGARUHNYA DALAM KAJIAN SOSIAL ISLAM - Abdullah, Faisal; Hosaini, Hosaini (Kependidikan Islam Fakultas Agama Islam, 2024)
Positivism as a philosophical school that developed rapidly in the 19th century has brought significant changes in the way we view science, especially in approaches to social phenomena. This article aims to analyze the development of positivism and its influence in Islamic social studies, by highlighting how this objective and empirical scientific approach interacts with the Islamic intellectual tradition. This study uses a qualitative method with a literature study approach, which includes a review of various main sources of positivism philosophy and classical and contemporary texts in Islamic social studies. Through an in-depth analysis of the literature, this article finds that although positivism has made an important contribution in introducing empirical methods into social studies, its application in an Islamic context often creates tensions, especially in relation to the debate between empirically based science and the more spiritual traditions of Islam. normative. This article concludes that although positivism can contribute to a more comprehensive understanding of social phenomena in Muslim societies, it is important to consider Islamic normative values ​​to avoid neglecting spiritual and ethical aspects in social analysis.